Harmonic suppression in branch‐line couplers based on slow‐wave transmission lines with simultaneous inductive and capacitive loading. Issue 10 (26th September 2018) - Selga, Jordi; Vélez, Paris; Coromina, Jan; Fernández‐Prieto, Armando; Bonache, Jordi; Martín, Ferran
Abstract: A compact branch‐line hybrid coupler with harmonic suppression based on slow‐wave microstrip lines is presented in this paper. These slow‐wave artificial transmission lines are implemented by simultaneously loading a host line with series inductors and shunt capacitors. By this means, the effective capacitance and inductance of the line are increased and, consequently, the phase velocity and signal wavelength are reduced. This slow‐wave effect, useful for device miniaturization, is applied to reduce the size of the coupler. Particularly, by implementing the reactive elements through capacitive patches and inductive strips, 64% size reduction, as compared to the conventional coupler, is achieved. Moreover, due to the filtering capability of the inductors and capacitors, the first and second harmonic responses of the coupler are completely suppressed. A detailed design methodology based on the schematic of the proposed slow‐wave transmission line is reported. The work includes a simple analysis to justify that two unit cells per transmission line section are necessary to suppress the harmonic bands leaving unaltered the coupler response in the region of interest. The fabricated device is fully planar, does not use vias, and the ground plane is kept unaltered.